mTORC1 and mTORC2 Kinase Signaling and Glucose Metabolism Drive Follicular Helper T Cell Differentiation - Zeng, Hu (Immunity, 2016)
Follicular helper T (Tfh) cells are crucial for germinal center (GC)formation andhumoraladaptiveimmunity. Mechanisms underlying Tfh cell differentiation in peripheral and mucosal lymphoid organs are incompletely understood. We report here that mTOR kinase complexes 1 and 2 (mTORC1 and mTORC2) are essential for Tfh cell differentiation and GC reaction under steady state and after antigen immunization and viral infection. Loss of mTORC1 and mTORC2 in T cells exerted distinct effects on Tfh cell signature gene expression, whereas increased mTOR activity promoted Tfh responses. Deficiency of mTORC2 impaired CD4(+) T cell accumulation and immunoglobulin A production and aberrantly induced the transcription factor Foxo1. Mechanistically, the costimulatory molecule ICOS activated mTORC1 and mTORC2 to drive glycolysis and lipogenesis, and glucose transporter 1-mediated glucose metabolism promoted Tfh cell responses. Altogether, mTOR acts as a central node in Tfh cells by linking immune signals to anabolic metabolism and transcriptional activity.